2023
DOI: 10.1101/2023.05.07.539748
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNA repair and anti-cancer mechanisms in the long-lived bowhead whale

Abstract: At over 200 years, the maximum lifespan of the bowhead whale exceeds that of all other mammals. The bowhead is also the second-largest animal on Earth, reaching over 80,000 kg. In spite of its very large number of cells, the bowhead is not highly cancer-prone, an incongruity termed Peto's Paradox. This has been explained by the evolution of additional tumor suppressor genes in larger animals, which is supported by research on elephants demonstrating expansion of the p53 gene. However, we show here that bowhead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 154 publications
0
3
0
Order By: Relevance
“…Among the positively selected and rapidly evolving genes, for example, are RIF1 , which cooperates with TP53BP1 to promote DNA repair by non-homologous end joining (NHEJ) in the G 1 and S phases of the cell cycle (Escribano-Díaz et al, 2013; Feng et al, 2013; Virgilio et al, 2013), the multifunctional exonuclease EXO1 , which is involved in DNA damage checkpoint progression, mismatch repair (MMR), translesion DNA synthesis (TLS), nucleotide excision repair (NER), and limits end resection of double-strand breaks thereby facilitating repair via error-free homologous recombination (HR) rather than error-prone NHEJ (Keijzers et al, 2018; Tomimatsu et al, 2017), MLH1 , part of PMS2 MMR complex that generates single-strand breaks near the mismatch and entry points for EXO1 to degrade the strand containing the mismatch (Kadyrov et al, 2006; Kansikas et al, 2011; Sacho et al, 2008), NEK4 , which regulates a unique ATM/ATR-independent DNA damage checkpoint and the induction of replicative senescence in response to double-stranded (DSB) DNA damage (Chen et al, 2011; Tomimatsu et al, 2017), KAT5 , an acetyltransferase that plays an essential role in DNA damage repair by acetylating and activating ATM and the canonical DSB repair pathway (Sun et al, 2005)and SAMHD1 which promotes DNA end resection to facilitate DSB repair by HR (Daddacha et al, 2017; Kapoor-Vazirani et al, 2022). Similarly, long-lived and cancer-resistant Bowhead whales, which have a maximum lifespan of over 200 years (George et al, 1999), have evolved cells that repair double-strand breaks with high efficiency and accuracy compared to many other mammals (Firsanov et al, 2023), suggesting that the evolution of DNA damage repair genes may be a common route to evolve cancer resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Among the positively selected and rapidly evolving genes, for example, are RIF1 , which cooperates with TP53BP1 to promote DNA repair by non-homologous end joining (NHEJ) in the G 1 and S phases of the cell cycle (Escribano-Díaz et al, 2013; Feng et al, 2013; Virgilio et al, 2013), the multifunctional exonuclease EXO1 , which is involved in DNA damage checkpoint progression, mismatch repair (MMR), translesion DNA synthesis (TLS), nucleotide excision repair (NER), and limits end resection of double-strand breaks thereby facilitating repair via error-free homologous recombination (HR) rather than error-prone NHEJ (Keijzers et al, 2018; Tomimatsu et al, 2017), MLH1 , part of PMS2 MMR complex that generates single-strand breaks near the mismatch and entry points for EXO1 to degrade the strand containing the mismatch (Kadyrov et al, 2006; Kansikas et al, 2011; Sacho et al, 2008), NEK4 , which regulates a unique ATM/ATR-independent DNA damage checkpoint and the induction of replicative senescence in response to double-stranded (DSB) DNA damage (Chen et al, 2011; Tomimatsu et al, 2017), KAT5 , an acetyltransferase that plays an essential role in DNA damage repair by acetylating and activating ATM and the canonical DSB repair pathway (Sun et al, 2005)and SAMHD1 which promotes DNA end resection to facilitate DSB repair by HR (Daddacha et al, 2017; Kapoor-Vazirani et al, 2022). Similarly, long-lived and cancer-resistant Bowhead whales, which have a maximum lifespan of over 200 years (George et al, 1999), have evolved cells that repair double-strand breaks with high efficiency and accuracy compared to many other mammals (Firsanov et al, 2023), suggesting that the evolution of DNA damage repair genes may be a common route to evolve cancer resistance.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the role of biochemical kinetics as regulators of developmental tempo. Species-specific mechanisms for extended lifespan are also reported, including the uniquely high efficiency and accuracy in DNA repair of the long-lived bowhead whale [50] . This is in line with the observations that somatic mutation rates are inversely correlated with lifespan across species [51] .…”
Section: Exploring Biological Time: Expansion Of the Zoo And Its Clocksmentioning
confidence: 99%
“…The bowhead whale thus benefits from a long life span because its cells are more proficient at repairing DNA damage. The study identified two proteins (CIRBP and RPA2) that are present at high levels in fibroblasts and are known to increase the fidelity and efficiency of DNA double-strand break (DSB) repair [ 34 ].…”
Section: The Dna Damage Response (Ddr) System Mediates the Rate Of Mu...mentioning
confidence: 99%